510 Niraparib outcomes in brca wild-type platinum sensitive recurrent ovarian cancer: a comparison of real-world data to the nova trial. (4th December 2020) - Cartwright, Douglas; Roxburgh, Patricia; Stanley, Barbara; Brown, Jennifer; Mclaren, Alistair; Coulter, Sarah; Forte, Carla; Glasspool, Ros
Abstract : Introduction/Background: The PARP inhibitor (PARPi), niraparib, is EMA approved for maintenance treatment in platinum-sensitive recurrent ovarian cancer. The eligibility criteria set out in niraparib licence are less stringent than those in the NOVA trial, therefore outcomes may be different in the real-world to those observed in trial patients. 1 The optimal management of patients after progression on PARPi is unknown and the relationship between platinum free interval and probability of response to platinum may be modified after PARPi therapy. To investigate this, we performed a retrospective analysis of real-world niraparib use and compared it to the NOVA trial. Methodology: Data was collected retrospectively for all women receiving maintenance niraparib for BRCA wild-type, platinum sensitive relapsed ovarian cancer between June 2017 and September 2019. Response to prior platinum, median progression-free survival (mPFS) after 1st and subsequent platinum, number of cycles of PARPi, dose, haematological toxicities, and PFS2I (start of subsequent therapy to physician assessed progression or death) were obtained through electronic records. Results: 37 patients received Niraparib in this timeframe. Median follow up was 16 months (range 5.7–37 months). Demographics were similar to previously published cohorts, however, only 11% (n=4) had a complete response (CR) to prior platinum therapy and 59% (n=22) had a partial response in comparison to 50% CR and 50% PR in the NOVA trial1. 35 (95%) of patients had progressed on niraparib at the time of data collection. The mPFS on niraparib was 4.4 months (95% CI 3.7 – 6.7 months) in comparison to 9.3 months in the NOVA study. Patients who met the NOVA trial radiological and serological response criteria, had a mPFS at 5.1 months (n = 19) compared to 3.9 months (n = 18). Dosing and toxicity data will be reported in full at the meeting. 31 patients received subsequent therapy, 19 (61%) were treated with paclitaxel, 9 (29%) were treated with platinum-based chemotherapy. Median PFS2I was 5.8 months for platinum sensitive disease and 3.5 months for platinum resistant disease. Conclusion: The real-world outcomes for niraparib treatment are worse than observed in the NOVA trial. Patients who meet NOVA trial eligibility criteria have better outcomes, however, these results are still inferior to those reported in the trial. Post PARP outcomes are poorer than expected in both platinum sensitive and platinum resistant settings. Strategies to effectively treat PARPi resistant disease are urgently needed. Disclosures: Dr R Glasspool: Grant funding for clinical trials from Boehringer Ingelheim, Lilly/Ignyta and Clovis. Consultancy fees, travel support and/or speaker fees for AstraZeneca, GSK/Tesaro, Clovis, Immunogen and Sotio. Site PI for studies sponsored by AstraZeneca, GSK/Tesaro, Clovis, Immunogen, Lilly and Pfizer. Reference: Mirza MR, et al . Niraparib Maintenance Therapy in Platinum-Sensitive, Recurrent Ovarian Cancer. N Engl J Med 2016;375 :2154–64.